Study of Office Facilities and Infrastructure Management in Supporting Administrative Activites at PT X - Anisa Puspita Sari; Henry Eryanto; Maulana Amirul Adha (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to determine the process of managing and utilizing office facilities and infrastructure in the Human Capital Department of PT X. The research method used is qualitative research descriptive analysis which involves researchers directly with the situation in the field so that researchers will more easily understand the processes carried out and the obstacles that occur in the management and utilization of office facilities and infrastructure carried out in the field. In this qualitative research, researchers observe objects in depth by collecting data about the object being studied and analyzing the data. Data collection techniques were obtained through observation, interviews, documentation and literature study. This research is expected to provide new knowledge regarding the process of managing and utilizing office facilities and infrastructure to support administrative activities carried out in the Human Capital Department of PT X.